STRUCTURAL ANALYSIS OF LINAC AND BRACHYTHERAPY BUNKER DESIGN (CASE STUDY: RADEN MATTAHER REGIONAL GENERAL HOSPITAL, JAMBI) - Syahroni, Alif Ihsan; Naibaho, Pio Ranap Tua; Sembiring, Kristina (University Muhammadiyah Jakarta, 2025)
The LINAC and Brachytherapy bunkers constructed at RSUD Raden Mattaher Jambi are part of a strategic healthcare development initiative by the Jambi Provincial Government. These bunkerstructures possess specialized characteristics to ensure maximum protection against radiationexposure, utilizing thick reinforced concrete and, in some areas, lead-lined layers. RadiationShielding Concrete (RSC), also known as heavyweight concrete, is used for this purpose, typicallyhaving a density greater than 2600 kg/m³. Designed to attenuate gamma rays, X-rays, andneutrons, the effectiveness of RSC depends significantly on its density. Studies indicate thatconcrete with densities between 3012–3820 kg/m³ achieves linear attenuation coefficients (μ)ranging from 0.224 to 0.265 cm⁻¹, demonstrating high shielding capability. During construction,deviations occurred between the Detail Engineering Design (DED) and the actual fieldimplementation (As-Built Drawing or ABD) due to site conditions and safety considerations. Thisstudy aims to analyze the structural differences between DED and ABD. Structural analysis wasconducted using ETABS software to obtain internal forces in the structural elements, followed bymanual verification. Results show that the columns are capable of resisting axial loads andmoments, with reinforcement ratios within the required 1%–6% of gross concrete area (Ag).Variations in internal forces were identified between DED and ABD. In the floor slab analysis, theDED design failed to meet flexural strength requirements (Mu > ϕMn), while the ABD designachieved sufficient nominal capacity (Mu < ϕMn), enhancing the structure’s performance underservice loads. Keywords: Bunker, Structural Analysis, LINAC, Brachytherapy, Radiation Shielding Concrete